Religious diversity in Canadian public schools rethinking the role of law - Dabby, Dia (Vancouver, BC UBC Press, 2022)
Everyday Law in Schools -- Litigation about Religion and Education: On (Un)Heard Voices -- Mediating Religious Diversity in Public Schools -- The Administrative Governance of Public Schools -- Relations of Belonging in Education to Mediate Diversity.
"Canadian public schools have long been entrusted with socializing children. Yet this duty can rest uneasily alongside religious diversity questions. Grounding its analysis in three seminal Supreme Court cases, Religious Diversity in Canadian Public Schools reveals complex legal processes that compress multidimensional conversations into an oppositional format and exclude the voices of children themselves. Dia Dabby contends that schools are in fact microsystems with the power to construct their own rules and relationships. This compelling work encourages a deeper conversation on how religion is mediated through public schools, inviting a critical reassessment of the role of law in education."--
Includes bibliographical references (pages 203-274) and index
Keywords: Religion in the public schools -- Law and legislation -- Canada; Education -- Law and legislation -- Canada; Freedom Of Religion -- Canada; Educational law and legislation; Freedom Of Religion; Religion in the public schools ; Law and legislation; Canada